The emergence of early Sufi piety and Sunni scholasticism : ʻAbdallah born al-Mubarak and the formation of Sunni identity in the second Islamic century - Salem, Feryal. (Islamic History and Civilization, 2016)
In the figure of ʿAbdallāh born al-Mubārak (118-181/736-797), we find a paragon of the fields of ḥadīth , zuhd , and jihād , as attested to by the large number of references to him in the classical Islamic texts. His superior rank as a ḥadīth transmitter earned him the title "commander of the faithful" in ḥadīth. He contributed to Islamic law at its early phases of development, practiced jihād, composed poetry, and participated in various theological discussions. In addition, Ibn al-Mubārak was a pioneer in writing on piety and was later regarded by many mystics as one of the earliest figures of Sufism. Ibn al-Mubārak's position during the formative period of Islamic thought illustrates the unique evolution of zuhd, ḥadīth, and jihād; these form a junction in the biography of Ibn al-Mubārak in a way that distinctively illuminates the second/eighth-century dynamics of nascent Sunnī identity. Furthermore, Ibn al-Mubārak's status as a fighter and pious figure of the Late Antique period reveals a great deal about the complex relationship between the early Muslim community and the religiously diverse setting which it inhabited. This critical and comprehensive monograph of ʿAbdallāh born al-Mubārak situates him within the larger context of the social and religious milieu of Late Antiquity. It explores the formation of Sunnī identity in the second Islamic century and demonstrates the way in which it manifested itself through networks of pious scholars who defined, preserved, and passed on what they understood to be normative Islamic practice and beliefs from one generation of Muslim intellectuals to another.